Evaluación de la Difusión y Alcance de la Rendición de Cuentas en el GAD Municipal Intercultural de Saraguro. - Byron Ariel, Silva Armijos (2025)
Accountability is a fundamental pillar of democratic governance, promoting transparency, citizen participation, and trust in public institutions. In Ecuador, Decentralized Autonomous Governments (GADs) are mandated to implement inclusive processes that cater to the characteristics of their communities. This study examines the dissemination and reach of accountability in the Intercultural Municipal GAD of Saraguro, focusing on communication mechanisms and citizens' perceptions of the transparency and clarity of the information provided. The research was conducted using a mixed-methods approach, combining interviews with five key GAD officials and surveys administered to 380 residents of Saraguro canton, encompassing both urban and rural areas. The results indicate that digital media, such as social networks and the website, are effective in reaching certain groups but face limitations in rural areas due to a lack of internet access. Furthermore, a significant portion of respondents believe that the GAD's reports are unclear and insufficiently detailed, making it difficult to evaluate public management. The study highlights the need to diversify communication channels by incorporating traditional media, such as radio and printed bulletins, which are more accessible to rural sectors and older adults. Additionally, using clear language and visual aids in reports would enhance their comprehensibility for all citizens. Increasing the frequency and level of detail in the reports could strengthen citizen participation, fostering a more transparent and collaborative relationship between the GAD and the community.